1996
DOI: 10.1038/ki.1996.437
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dialysis on plasma lipid peroxidation products and antioxidant levels

Abstract: In patients with end-stage renal failure (ESRF), the incidence of atherosclerosis and cancer is increased. The importance of lipid peroxidation (LPO) products in the pathogenesis of these complications has recently been emphasized. The LPO products malondialdehyde (MDA) and hexanal, lipophilic antioxidants and erythrocyte glutathione (GSH) were estimated in 10 pediatric hemodialysis (HD) patients before and after HD and in 11 peritoneal dialysis (CPD) patients. Before HD, MDA was elevated [median (interquartil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
50
2
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 29 publications
8
50
2
1
Order By: Relevance
“…In our previous studies [6,20], we indicated a defective antioxidant defense during the process of HD, due to the reduction of antioxidants and elevated lipid peroxidation in patients on HD in agreement with the other studies [7,9,[12][13][14]21]. However, a study has shown decrease in the serum levels of MDA compared to control group [22]. While in some studies, antioxidants activity [23] and lipid peroxidation have no change [24].…”
Section: Discussionsupporting
confidence: 54%
“…In our previous studies [6,20], we indicated a defective antioxidant defense during the process of HD, due to the reduction of antioxidants and elevated lipid peroxidation in patients on HD in agreement with the other studies [7,9,[12][13][14]21]. However, a study has shown decrease in the serum levels of MDA compared to control group [22]. While in some studies, antioxidants activity [23] and lipid peroxidation have no change [24].…”
Section: Discussionsupporting
confidence: 54%
“…This process could lead to the peroxidative stress during HD. This oxidative effect of HD, however, is still controversial [8, 9, 10]. Many of the previous studies in this field evaluated lipid peroxidation using TBARS.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, direct evidence for in vivo oxidative stress in HD patients was almost entirely limited to the measurement of lipid peroxidation by-products such as malondialdehyde and other thiobarbituric acid-reactive substances (22). Despite the observation that proteins are highly susceptible to oxidative stress, there have been few reports of the production of oxidatively modified proteins in HD procedures.…”
Section: Discussionmentioning
confidence: 99%